Kompetisi Pasar Dan Transaksi Di Era Globalisasi - Kholishudin Kholishudin (Journal of Islamic Banking, 2023)
In the era of globalization, market development is becoming more complex and dynamic with the existence of information technology that allows companies to enter the global market. This study aims to analyze the factors that can affect the market and competitive rank, as well as the relationship between the two. The research method used in this research is a literature study with a qualitative approach. Data sources in this study are from various reading sources such as books, journals and literature related to the research topic. The results showed that information technology, globalization, government regulation, and consumer behavior are the main factors for the formation of markets and competitive spaces. Case studies in the smartphone industry such as Samsung, Apple, and Xiaomi show that using the right strategy allows companies to achieve significant competitive advantages. In conclusion, the use of information technology, adapting to globalization, complying with regulations, and understanding consumer preferences are very important to increase market competitiveness.